(untitled) (Scientific journal of the Fergana State University, 2024)
This article explains and analyzes words borrowed from Arabic in the work of the great thinker Alisher Navoi “Nasaim ul-Mukhabbat”. The main purpose of writing this article is to analyze and explain the meaning of words borrowed from Arabic in A. Navai’s work “Nasaim ul-Mukhabbat”. In the process of writing the article, verbal analysis, contextual analysis, historical and linguistic approach, and comparative methods were used.